Access to School Management in the Education System. Development by Educational Administrations of the Merit-Based Competition Procedure - Palacios Garraza, Ana (Avances en Supervisión Educativa, 2024)
Taking into consideration the important role that the School Management can play in the educational quality of the educational centers they lead and, consequently and exponentially, in the educational system of the country, it is essential to grant the importance it deserves to the procedure of access to it in order to achieve the success of the educational system. The purpose of this article is to offer an analytical view of the development of the merit-based competitive examination procedure by the Education Administrations of the different Autonomous Communities, under the margin of autonomy granted by Organic Law 3/2020, of December 29, which amends Organic Law 2/2006, of May 3, on Education (LOMLOE). After a brief normative and scientific contextualization on access to school management, an analysis of the articles of the LOMLOE referring to selection, requirements and procedure for access to management is carried out. Then, the differences established by the Educational Administrations are examined, both in the requirements to participate in the merit-based competition and in the selection process of school principals, which consists of the evaluation of the management project and, if applicable, in the evaluation of the merits presented by the candidates.